Gilligan’s Persfective Morality Toward Women in Short Stories Which Published in Kompas From 2010-2015 - Aji Septiaji; Risma Khairun Nisya (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research focuses on Giligan’s morallity concept that relate to three aspects of woman’s attitude which include pre-conventional (individualist), conventional (willing to sacrifice), and pasca-conventional (determine of decision). This research used content analysis method. There were 23 of 130 short stories from Kompas that taken as data of this research. The result of this research indicates that individualist of woman attitude is caused by her ego, safety, and anxiety. Willing of sacrife attitude is caused by pity and carinng; determine of decision is caused by cause and effect relationship which support by guilty, happiness, doubt, tough, hopeless, and desperate. Keywords: morality, Gilligan, women, short stories, kompas Abstrak Penelitian ini berfokus pada moralitas Gilligan mengenai tiga aspek sikap perempuan yaitu prakonvensional (individualis), konvensional (rela berkorban), pascakonvensional (penentuan keputusan). Metode penelitian menggunakan analisis isi. Data yang dianalisis dari Kompas berjumlah 23 dari 130 cerpen tahun 2010-2015. Hasil penelitian menunjukkan sikap individualis perempuan disebabkan oleh kepentingan sendiri, rasa aman, dan khawatir. Sikap berkorban disebabkan oleh rasa iba dan kasih sayang; penentuan keputusan disebabkan oleh hubungan timbal balik dengan disertai rasa sesal, bahagia, bimbang, yakin, putus asa, dan pasrah. Kata kunci: moralitas, Gilligan, perempuan, cerita pendek, kompas